2022
DOI: 10.3390/jcm11113194
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Antibiotic Use for COVID-19: Facts and Rationales Assessed through a Mixed-Methods Study

Abstract: It is well known that during the coronavirus disease 2019 (COVID-19) pandemic, antibiotics were overprescribed. However, less is known regarding the arguments that have led to this overuse. Our aim was to understand the factors associated with in-hospital antibiotic prescription for COVID-19, and the rationale behind it. We chose a convergent design for this mixed-methods study. Quantitative data was prospectively obtained from 533 adult patients admitted in six hospitals (services of internal medicine, infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…They found that the drug contents in wastewater varied with the type of hospital, and ARGs were specific to the microbial species in the wastewater. Significant differences have also been noted in the dosages and types of drugs even in different clinical departments in the same hospital and among different doctors in the same department [14]. Antibiotics, such as amoxicillin, cefuroxime, levofloxacin, azithromycin, and metronidazole, are routinely used to treat infections.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the drug contents in wastewater varied with the type of hospital, and ARGs were specific to the microbial species in the wastewater. Significant differences have also been noted in the dosages and types of drugs even in different clinical departments in the same hospital and among different doctors in the same department [14]. Antibiotics, such as amoxicillin, cefuroxime, levofloxacin, azithromycin, and metronidazole, are routinely used to treat infections.…”
Section: Introductionmentioning
confidence: 99%
“…20 Other reports during the pandemic showed that azithromycin consumption increased up to 3 times compared to the pre-COVID period. 1921…”
Section: Discussionmentioning
confidence: 99%
“…Through bibliometric analysis and scientific knowledge mapping of the field of depression research during COVID-19, the following aspects may also be of interest in the future. First, most articles in the field of depression research during COVID-19 have been studied using quantitative research methods, and few have been studied using a mixture of qualitative and quantitative research methods ( 108 , 109 ). Second, by reading the articles, it was established that most of the scales used to assess depression in the field articles were developed before the pandemic.…”
Section: Discussionmentioning
confidence: 99%